Đánh giá năng suất và hiệu quả ngành bảo hiểm phi nhân thọ tại Việt Nam sử dụng chỉ số Färe-Primont - Nguyễn Phương, Anh; Hoàng Thị Lan, Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
The insurance industry plays a vital role in promoting economic growth, ensuring financial stability, and efficiently allocating risks. This study analyzes the productivity and efficiency of non-life insurance companies in Vietnam during the period 2019–2021, employing the Färe-Primont productivity index. The findings indicate that Vietnam’s non-life insurance companies maintain high technical and mix efficiencies, while overall and scale efficiencies remain relatively low. Over the period 2019–2021, despite a decline in technological progress in the industry, overall productivity and operational efficiency recorded slight improvements, driven by enhanced scale efficiency. To boost productivity and overall efficiency, non-life insurance companies should prioritize solutions to optimize scale efficiency and accelerate technological progress.
Keywords: Technical efficiency; Mix efficiency; Scale efficiency; Total factor productivity; Färe-Primont index; Non-life insurance